Flavonoids in Astragalus corniculatus - Krasteva,Ilina (2008)
Nine flavonoids were identified in aerial parts of Astragalus corniculatus Bieb. (Fabaceae) by liquid chromatography coupled with ionspray mass spectrometry in the tandem mode (LC/MS/MS) with negative ion detection. Vitexin, orientin and eriodictyol-7-O-glucoside are obtained for the first time in genus Astragalus L, and isorhamnetin-3-O-glucoside in the species.